Patient Awareness of Peripheral Artery Disease and Its Risk Factors: A Quantitative Study in Jordan - Aldergham, Muath; Alfouri, Areeg (Journal of Neonatal Surgery, 2025)
This study addresses patients’ awareness of PAD, or peripheral artery disease, and its related risk factors, such as diabetes, smoking, high cholesterol, and high blood pressure, which are factors that contribute significantly to the development of the disease. The study aims to measure the level of knowledge of patients in Jordan about this disease, and to study the impact of health awareness on prevention and early diagnosis. By reviewing previous studies, it was found that there is a global and regional lack of awareness of PAD, as many studies in developed countries have shown that less than a third of patients are aware of their condition. In developing countries, including Jordan, research on this topic is limited. The study uses a questionnaire tool based on a three-point Likert scale to measure patients’ knowledge, attitudes, and health practices related to the disease. The study's findings demonstrated that the degree of awareness of participants about PAD was generally average, with differences in knowledge, attitudes, and health practices among participants. The results highlighted the importance of increasing awareness of the risks and factors affecting the disease and encouraging preventive health practices.